Politik Pendidikan: Studi Kasus Formulasi Kebijakan Alokasi 20 Persen APBN Untuk Pendidikan - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Andhyka Muttaqin (FISIP UWP, 2010)
This research stems from the emergence of an issue about 20 percent of the budget for education, followed by the Constitutional Court Decision No. 026/PUU-III/2005 dated March 22, 2006 which states for the education budget has not yet reached 20 percent as specified in the 1945 Constitution, the budget will always be against the Constitution in 1945. Researchers trying to come up how the trip actually 20 per cent allocation policy formulation national budget for education and political dynamics that exist therein. As the basis is the fourth amendment to the 1945 Constitution article 31 paragraph (4) which states